1964
DOI: 10.1113/jphysiol.1964.sp007364
|View full text |Cite
|
Sign up to set email alerts
|

The action of peptides on the adrenal medulla. Release of adrenaline by bradykinin and angiotensin

Abstract: The present experiments show that bradykinin and angiotensin are potent releasers of the medullary hormones, probably mainly adrenaline, from the suprarenal glands. Angiotensin is more potent in this respect than any other known substance. These findings were the outcome of a chance observation made when assaying bradykinin by its depressor action on the arterial blood pressure of the cat. On trying to render the assay more sensitive by removing the abdominal viscera and injecting the bradykinin through the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
97
3
2

Year Published

1965
1965
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(116 citation statements)
references
References 5 publications
14
97
3
2
Order By: Relevance
“…Thus, the pressor potency was reduced by treatment with the catecholamine depleting substances, reserpine and syrosingopine, and was restored by infusions of catecholamines. Similarly, inhibition of monoamine oxidase which has been shown to increase peripheral levels of catecholamines (Goldberg & Shideman, 1962;Sanan & Vogt, 1962) (Feldberg & Lewis, 1964, 1965Vane, 1969 (Bickerton & Buckley, 1961) and via central vagal inhibition (Scroop & Lowe, 1968). The failure of both pempidine and bethanidine to reduce the angiotensin pressor responses in the present experiments argues against a significant central component to the response.…”
contrasting
confidence: 38%
“…Thus, the pressor potency was reduced by treatment with the catecholamine depleting substances, reserpine and syrosingopine, and was restored by infusions of catecholamines. Similarly, inhibition of monoamine oxidase which has been shown to increase peripheral levels of catecholamines (Goldberg & Shideman, 1962;Sanan & Vogt, 1962) (Feldberg & Lewis, 1964, 1965Vane, 1969 (Bickerton & Buckley, 1961) and via central vagal inhibition (Scroop & Lowe, 1968). The failure of both pempidine and bethanidine to reduce the angiotensin pressor responses in the present experiments argues against a significant central component to the response.…”
contrasting
confidence: 38%
“…The possibility still remains however that the phenomenon represents true tachyphylaxis, the organs responding less to the same concentration of the active agent. Feldberg & Lewis (1964) showed that bradykinin releases catechol amines from the adrenal medullae in the anaesthetized cat. If this occurs also in man, it is possible that the level of circulating catechol amines may have risen as the infusion of bradykinin continued in the present experiments and that this may have led to the observed secondary increase in systemic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Ang II facilitates sympathetic transmission, inhibits norepinephrine reuptake (Starke, 1977) and releases catecholamine from the adrenal medulla (Feldberg & Lewis, 1964). Additionally, the renin-angiotensin system modulates the kallikrein-kinin system, a regulatory system involved in a multitude of physiologic and pathologic conditions.…”
Section: Introductionmentioning
confidence: 99%